2018
DOI: 10.3390/jimaging5010005
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Modal Medical Image Registration with Full or Partial Data: A Manifold Learning Approach

Abstract: Multi-modal image registration is the primary step in integrating information stored in two or more images, which are captured using multiple imaging modalities. In addition to intensity variations and structural differences between images, they may have partial or full overlap, which adds an extra hurdle to the success of registration process. In this contribution, we propose a multi-modal to mono-modal transformation method that facilitates direct application of well-founded mono-modal registration methods i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 75 publications
0
23
0
Order By: Relevance
“…They demonstrated that the network could rapidly and accurately quantify registration performance. Multi-grid Inference [163] Brain 3D-3D MR-US Rigid LSTM [8] Brain 2D-2D CT, T1, T2, PD Rigid Manifold Learning [165] Brain, Abdomen 2D-3D CT-PET, CT-MRI Deformable CAE, DSCNN [178] Spine 3D-2D 3DCT-Xray Rigid FasterRCNN [54] Brain 2D-2D T1-T2, T1-PD Deformable FCN [183] Spine 3D-2D 3DCT-Xray Rigid Domain adaptation…”
Section: Registration Validation Using Deep Learningmentioning
confidence: 99%
“…They demonstrated that the network could rapidly and accurately quantify registration performance. Multi-grid Inference [163] Brain 3D-3D MR-US Rigid LSTM [8] Brain 2D-2D CT, T1, T2, PD Rigid Manifold Learning [165] Brain, Abdomen 2D-3D CT-PET, CT-MRI Deformable CAE, DSCNN [178] Spine 3D-2D 3DCT-Xray Rigid FasterRCNN [54] Brain 2D-2D T1-T2, T1-PD Deformable FCN [183] Spine 3D-2D 3DCT-Xray Rigid Domain adaptation…”
Section: Registration Validation Using Deep Learningmentioning
confidence: 99%
“…This idea has been applied with high quality data 24,36 , but the multi modality registration problem is more challenging when extra signals are present. Related work 37,38 has approached this challenge, but have been restricted to simple deformations. The method we develop jointly addresses each of these challenges: estimating arbitrary 3D and 2D deformations, predicting locations of extra signal by treating them as missing data in an Expectation Maximization setting as in [38][39][40] , and modeling different contrasts by synthesizing them in a generative framework.…”
Section: Discussionmentioning
confidence: 99%
“…As slice spacing decreases, it is hard to distinguish adjacent slices, which results in the deviation of many multimodal similarity algorithms. To verify our method's validation, we performed modality-group similarity experiment with 4 different methods: (1) the proposed method in [8] using entropy (M1 function) images, (2) the method using Laplacian method in manifold learning [14], (3) multimodal registration with mutual information (MI) [4], and (4) traditional method with mean absolute differences (MAD). e above result of the experiment is illustrated on Tables 2-4.…”
Section: Modality-group Similarity Experiments On Rigidmentioning
confidence: 99%
“…However, it focuses on space location relationship and loses sight of potential richness. Most recently, in 2019, Bashiri et al [14] expressed the descriptor set in high dimensional space, studying potential structures of an image through Laplacian eigenmap. Nonlinear dimensionality reduction from manifold space will result in the loss of original potential information.…”
Section: Introductionmentioning
confidence: 99%